Binary Intensity Modulation and Hybrid Ternary Modulation Applied to Multiplexing Objects Using Holographic Data Storage on a PVA/AA Photopolymer - Elena Fernandez; Rosa Fuentes; Andrés Márquez; Augusto Beléndez; Inmaculada Pascual (International Journal of Polymer Science)
Holographic data pages were multiplexed in a polyvinyl alcohol/acrylamide photopolymer and a liquid crystal device was used to modify the object beam and store objects in the material. A peristrophic multiplexing method was used to store a large number of objects in the same spot of the material. The objects were stored using two different modulations: binary intensity modulation and hybrid ternary modulation. Moreover, the bit error rate (BER) of the images was calculated in order to compare which modulation is most appropriate to be used for holographic data storage.